Pengembangan Perangkat Pembelajaran mengacu Model Creative Problem Solving berbasis Somatic, Auditory, Visualization, Intellectually - Wijayanti, Septiana; Sungkono, Joko (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
This study aims to develop the valid, practical, and effective teaching instruments by using Creative Problem Solving (CPS) learning model with Somatic, Auditory, Visualization, and Intellectually (SAVI) based. This method of this study is RnD (Research and Development) which uses 4 D (Define, Design, Develop, and Development) learning model from Thiagarajan. But, this phase of the study is not spreading the developing result of the teaching instrument yet. This study produces learning instruments such as lesson plan (RPP), learning module, and students’ worksheet (LKS). The result of this study shows that 1) learning instruments by using CPS learning model with SAVI based such as lesson plan, learning module, and student’s worksheet includes in good category based on the expert judgement generally, 2) students and teacher’s response toward the learning by using CPS learning model with SAVI based show that they are interested in learning process, new learning model which is not used before, and they are also interested in the student’s worksheet and learning module, and 3) CPS learning model with SAVI based is effective to use in learning distance in space. From this result of the study, it can be concluded that the developed learning instrument is valid, practical, and effective.Keywords: CPS; Development;Learning Instrument; SAVI.